2023
DOI: 10.3389/fneur.2023.1201932
|View full text |Cite
|
Sign up to set email alerts
|

Useful outcome measures in INPH patients evaluation

Laura Mori,
Federica Collino,
Annalisa Marzi
et al.

Abstract: IntroductionIdiopathic normal pressure hydrocephalus (INPH) is a neurological disorder that is potentially reversible and clinically characterized by a specific triad of symptoms, including gait disturbance, cognitive disorders, and urinary incontinence. In INPH assessment, the most commonly used test is the Timed Up and Go test (TUG), but a more comprehensive assessment would be necessary. The first aim of the present study is to verify the sensitivity of a protocol with both clinical and instrumental outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Our study found a strong correlation between static and dynamic steady-state balance at pre-CSFTT in patients with iNPH. Until now, assessments of gait function, which indicate dynamic steady-state balance, have been used as diagnostic and evaluative tools for iNPH ( 4 , 5 , 40 , 41 ). This study suggests that measuring COP parameters during quiet standing, which assesses static steady-state balance, may be useful a potential diagnostic biomarker in iNPH patients who do not walk independently or who frequently fall.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a strong correlation between static and dynamic steady-state balance at pre-CSFTT in patients with iNPH. Until now, assessments of gait function, which indicate dynamic steady-state balance, have been used as diagnostic and evaluative tools for iNPH ( 4 , 5 , 40 , 41 ). This study suggests that measuring COP parameters during quiet standing, which assesses static steady-state balance, may be useful a potential diagnostic biomarker in iNPH patients who do not walk independently or who frequently fall.…”
Section: Discussionmentioning
confidence: 99%